Edukasi Pembuatan Permen Jelly Dari Buah Okra (Abelmoschus Esculentus L.) Untuk Pencegahan Penyakit Diabetes Melitus Di Sma 7 Plus Kota Bengkulu - Dharmayanti, Luky; Herlina; Sesi Hervitriwita; Agnes Monica; Della Triananda; Yoserizal Sesar (Gayaku Publisher, 2024)
Okra (Abelmoschus esculentus L.) Is a plant that comes from the malvacae family which is known as lady finger. okra also contains phenols and flavonoids which have antioxidant and anti-diabetic effects, the fiber contained in okra is suitable for processing as a chewy textured food such as jelly drink.The purpose of this service is for students of SMAN 7 Bengkulu city to know the benefits of okra fruit and its processing in the form of jelly candy which can prevent diabetes mellitus.The method used in this service is by distributing brochures and questionnaires to students of SMAN 7 Bengkulu City and brief material presentations about okra fruit and its processing.The results of the activity obtained were 27 students who liked the taste of jelly candy and 3 students who didn't like it.There were 23 students who liked the aroma and 7 students did not like the aroma.There were 17 students who liked the color and 13 students liked the color a little.